Chapter Prodolžat'/prodolžit': una strana coppia - Zoricic, Nika (Biblioteca di Studi Slavistici, 2016)
The aim of the present article is to investigate the aspectual status of the Russian verbs prodolzhat' and prodolzhit'. It is shown that the form prodolzhal is very frequently used in the past tense as a perfective verb with inchoative value in sequences of single events. Furthermore, the diachronic analysis of the examples reveals that, in the past tense, the form prodolzhit' until the 1990s was much less commonly used than the form prodolzhat'. Taking into account these results, in the article is hypothesized that the form prodolzhat' in the past tense may be considered a biaspectual verb.